Factors Affecting Firm Value - Silitonga, Juliarta Elisabeth; Talitha Nabila; Muhammad Khoiri Luthfi; Dona Olivia Sihombing; An Suci Azzahra (Indonesian Journal Publisher, 2025)
This Study aims to analyze the effect of Debt to Equity Ratio (DER), Divident Payout Ratio (DPR) and Price to Book Value (PBV) on firm value in the energy sector listed on the Indonesia Stock Exchange. Using data for the period 2019 to 2023 as a sample, this study examines the relationship between these three financial ratios and firm value as measured by Price to Book Value (PBV). The analysis methods used are classical assumption test, multiple linear regression, descriptive statistics, coefficients of determinations, t test and f test to determine the significant effect of each variable on firm value.